164 THE DEVELOPMENT AND IMPLEMENTATION OF A SMALL GROUP INTERACTION COMPONENT FOR THE PEDIATRIC CLERKSHIP. (1st January 2005) - English, M. R.; Yang, T.; Chauvin, S.
Abstract : Several studies have shown that students prefer using small group methods over traditional lectures for developing clinical reasoning skills. Prior to July 2003, a major component of the third year pediatric clerkship at LSUHSC was a series of lectures. Significant student dissatisfaction and an interest in problem-based learning (PBL) led the clerkship directors to develop a new program, entitled Pediatric Forums. Small groups of 5 to 7 students meet with a faculty facilitator 6 times throughout the 8-week clerkship. An agenda established by the clerkship directors and based on a national pediatrics curriculum is assigned to each session to ensure similarity of content across groups. Several small group sessions involve case-based activities and include many elements of PBL. Faculty leaders are instructed in small group facilitation methods and are expected to utilize these techniques during these sessions. The effectiveness of this change in the clerkship was studied during the first year of implementation, using clerkship evaluations, voluntary questionnaires, and review of examination scores. Overall our students prefer the forums to the lecture series. Students report an increase in the development of and feedback on their clinical problem solving skills. Examination scores and patient contact time have remained unchanged. Involved faculty facilitators have reported that although the Forums program is time-consuming, it is an effective educational experience for the students. We conclude that the Pediatric Forums program is an effective educational component of the clerkship. We will elaborate on the results of our study, discuss challenges faced in developing this new curricular project, and review plans for future research endeavors regarding this program.